Podwójne zęby nadliczbowe w przednim odcinku szczęki u 9-letniego chłopca - opis przypadku = Double teeth overtime in the front stretch of the jaws on the 9-year-old boy - a description of the case - Szczepkowska, Aleksandra; Osica, Piotr; Janas-Naze, Anna (Journal of Education, Health and Sport, 2016)
Szczepkowska Aleksandra, Osica Piotr, Janas-Naze Anna. Podwójne zęby nadliczbowe w przednim odcinku szczęki u 9-letniego chłopca - opis przypadku = Double teeth overtime in the front stretch of the jaws on the 9-year-old boy - a description of the case. Journal of Education, Health and Sport. 2016;6(5):111-118. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51318 http://ojs.ukw.edu.pl/index.php/johs/article/view/3513 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.04.2016. Revised 29.04.2016. Accepted: 11.05.2016. Podwójne zęby nadliczbowe w przednim odcinku szczęki u 9-letniego chłopca - opis przypadku Double teeth overtime in the front stretch of the jaws on the 9-year-old boy - a description of the case Aleksandra Szczepkowska, Piotr Osica, Anna Janas-Naze Zakład Chirurgii Stomatologicznej UM w Łodzi Kierownik: dr hab. n. med. prof. nadzw. Anna Janas-Naze Adres do korespondencji: Aleksandra Szczepkowska Zakład Chirurgii Stomatologicznej UM w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: aleksandra.szczepkowska@gmail.com tel. 42 675 75 71 Praca finansowana przez Uniwersytet Medyczny w Łodzi w ramach działalności statutowej nr 503/2-163-01/503-21-001 Streszczenie W pracy przedstawiono przypadek postępowania chirurgicznego, przeprowadzonego w znieczuleniu ogólnym, u 9-letniego pacjenta z dwoma zębami nadliczbowymi w okolicy zatrzymanych zębów 11 i 21. Słowa kluczowe: zęby nadliczbowe, zęby zatrzymane, znieczulenie ogólne. Abstract The work shows a case of surgical procedure, performed under general anesthesia, the 9-year-old patient with two chattering excessive working around retained teeth 11 and 21. Keywords: teeth, extra teeth, a general anesthetic.